Competitive aminal formation during the synthesis of a highly soluble, isopropyl-decorated imine porous organic cage. Issue 25 (10th March 2023) - Kearsey, Rachel J.; Tarzia, Andrew; Little, Marc A.; Brand, Michael C.; Clowes, Rob; Jelfs, Kim E.; Cooper, Andrew I.; Greenaway, Rebecca L.
Abstract : An imine-derived isopropyl-functionalised POC was synthesised over competitive aminal formation by introducing an additional amine in the assembly process. Abstract : The synthesis of a new porous organic cage decorated with isopropyl moieties (CC21) was achieved from the reaction of triformylbenzene and an isopropyl functionalised diamine. Unlike structurally analogous porous organic cages, its synthesis proved challenging due to competitive aminal formation, rationalised using control experiments and computational modelling. The use of an additional amine was found to increase conversion to the desired cage.